High Performance Liquid Chromatography (HPLC) Fingerprinting, Mineral Composition and In Vitro Antioxidant Activity of Methanol Leaf Extract of Synsepalum dulcificum (Sapotaceae) - Tajudeen Olabisi Obafemi & , Afolabi Clement Akinmoladun, Mary Tolulope Olaleye, Amos Onasanya, Kayode Charles Komolafe, John Adeolu Falode, Aline Augusti Boligon, Margareth Linde Athayde (Journal of Applied Pharmaceutical Science, 2017)
This study was carried out to identify the phytochemicals and in vitro antioxidant activity of methanol leaf extract of Synsepalum dulcificum (MSD). Standard protocols were used to evaluate the total phenols, total flavonoids and total antioxidants content of the extract. Nitric oxide (NO), hydroxyl radical (OH), ABTS•+and 2,2-diphenyl -1-picrylhydrazyl (DPPH) radicals scavenging activity, inhibition of lipid peroxidation and the ability of MSD to chelate ferrous ion as well its reductive potential were also evaluated. High Performance Liquid Chromatography (HPLC) was used to confirm the presence of polyphenols and carotenoids. Results showed the presence of flavonoids, saponins, terpenoids and cardiac glycosides in the extract. Among others, appreciable levels of potassium, calcium, sodium and magnesium were detected in the extract. The IC50 of the extract for DPPH, NO, OH-, and ABTS•+ radicals scavenging assays were 139.45 μg/ml, 119.17 μg/ml, 147.65 μg/ml, and 135.83 μg/ml respectively. It could be inferred that MSD showed appreciable in vitro antioxidant activity and could be useful in preventing and ameliorating diseases in which free radicals are implicated.
Keywords: Flavonoids, reducing power, trolox, free radical, biochemical.